Implementasi Sistem Informasi Manajemen Dalam Strategi Pemasaran Digital Melalui Konten Instagram - Riana Amalia Sacrivi; Dea Ananda; R. Taufiq Nur Muftianto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This research discusses the integration of Management Information System (MIS) in digital marketing strategies through the Instagram platform. Using a qualitative approach with a case study, the research elaborates on the utilization of MIS in collecting and analyzing customer data and its impact on digital marketing effectiveness. The main findings indicate that MIS plays a crucial role in enhancing understanding of customer behavior, facilitating team coordination, and expediting marketing decision-making. However, challenges such as resource availability and employee training are also identified. The results of this study provide in-depth insights into the role of MIS in the context of Instagram digital marketing and offer practical recommendations to enhance MIS implementation and digital marketing strategy efficiency.